(untitled) (REVISTA NODO, 2017)
Understanding the relationships and links between architecture and territory concepts from the discipline of architecture approach, it contributes to the academic debate on the role of territory in the praxis and to reduce the conceptual gap in academic and professional production. %e preliminary delineation of binding axes is the result of the investigation around some publications of specialized authors, as well as conceptual validation by the interview in the professional field and by survey in the academic field. %e discussion considers the disciplinary and conceptual autonomy, the complexity of interactions within a scheme articulated by the project outline and the notion of place from the object, and acting under guiding principles of the practice and mainstreaming of habitat and landscape. Keywords: Territory; Architecture; Urbanism; Proyect; Place; Habitat; Planning; Landscape; History; Site.